Implementasi Teknik Masking Dalam Pembuatan Video Company Profile PT Tropical Electronic - Aziza Az Zahrawani; Maidel Fani (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2021)
PT Tropical Electronic is the one of the companies that contributed to industrial growth in Batam City. The company which is manufacturing digital scales is a member of the Digi Group. The company profile video was created to introduce PT Tropical Electronic as a company that manufactures digital scales in Indonesia. Also, the video will be made with the agreement of the company. The video will be made based on the Villamil Molina method which consists of 5 stages, there are development, pre-production, production, post-production, and delivery. For editing, PT Tropical Electronic's company profile video will be edited by applying masking techniques with blurred effects. Furthermore, quantitative research was carried out by distributing questionnaires to get audience response to PT Tropical Electronic's company profile video. The questionnaire was made in the form of attitude measurement using a Likert Scale.